Kesetaraan Gender dalam Ibadah dan Pendidikan untuk Meningkatkan Kualitas Kedisiplinan Santri Pondok Pesantren di Kabupaten Maros - St. Fauziah; Nurhidayah (Jurnal Ragam Pengabdian, 2026)
This research aims to analyze the condition of gender equality in the aspects of worship, education and discipline of male and female students in three Islamic boarding schools, namely Hj. Haniah, Al-Mubarak, and Al-Ishlah. A qualitative descriptive approach using the phenomenological method was used to reveal the experiences of students regarding the differences in rules and treatment applied in each Islamic boarding school. The research results show that equality in the implementation of worship has not been fully realized, marked by different rules for male and female students, such as the obligation to pray Dhuha which only applies to male students at Islamic Boarding School Hj. Haniah, as well as differences in sanctions for violations of worship at the Al-Mubarak Islamic Boarding School. In terms of education, the three Islamic boarding schools do not provide extracurricular and special education programs evenly. For example, pencak silat is only attended by male students at Al-Mubarak and Al-Ishlah, while female students at Islamic Boarding School Hj. Haniah takes takhassus classes non- regularly. In terms of discipline, each Islamic boarding school has different rules that are adapted to the characteristics of the students, but still shows gender bias. This research concludes that there are still differences in treatment based on gender in terms of worship, education, and in achieving discipline in the three Islamic boarding schools